2015
DOI: 10.1104/pp.15.01409
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and Companion Cell-Specific Overexpression of AVP1, Encoding a Proton-Pumping Pyrophosphatase, Enhances Biomass Accumulation, Phloem Loading, and Long-Distance Transport

Abstract: Plant productivity is determined in large part by the partitioning of assimilates between the sites of production and the sites of utilization. Proton-pumping pyrophosphatases (H + -PPases) are shown to participate in many energetic plant processes, including general growth and biomass accumulation, CO 2 fixation, nutrient acquisition, and stress responses. H + -PPases have a well-documented role in hydrolyzing pyrophosphate (PPi) and capturing the released energy to pump H + across the tonoplast and endomembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 75 publications
3
64
0
1
Order By: Relevance
“…H + ‐PPase has been considered as a yield‐enhancing factor (Gonzalez et al ., 2010; Khadilkar et al ., 2016). Increased biomass, especially root system, has been reported in plants overexpressing type I H + ‐PPases, under deficiencies of phosphate (Gaxiola et al ., 2012; Pei et al ., 2012; Yang et al ., 2007, 2014) and nitrogen (Lv et al ., 2015; Paez‐Valencia et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…H + ‐PPase has been considered as a yield‐enhancing factor (Gonzalez et al ., 2010; Khadilkar et al ., 2016). Increased biomass, especially root system, has been reported in plants overexpressing type I H + ‐PPases, under deficiencies of phosphate (Gaxiola et al ., 2012; Pei et al ., 2012; Yang et al ., 2007, 2014) and nitrogen (Lv et al ., 2015; Paez‐Valencia et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the high expression of IbVP1 in young storage root indicates an important function related to storage root development (Figure 2). These results further confirmed that up‐regulation of H + ‐PPase promoted translocation of photosynthates from leaf to root, as hypothesized previously (Gaxiola et al ., 2012; Hermans et al ., 2006; Khadilkar et al ., 2016; Paez‐Valencia et al ., 2011). A recent study also demonstrated that increased sucrose accumulation was required for the regulation of auxin‐mediated Fe deficiency in plants (Lin et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] However, H C -PPase also saliently localizes at the vascular tissues of plants, wherein this protein is predominantly localized at the plasma membrane (PM) of the sieve element companion cell (SE-CC) complexes. 8,[11][12][13] Thermodynamic, 14 genetic, immunohistochemical, and physiological evidence 8,15,16 is consistent with a reverse PPi synthase activity of H C -PPase at the PM in the phloem, where it plays an important role in PPi homeostasis and photosynthate partitioning. 10,[15][16][17] We contend that the magnitude of proton gradients associated with the tonoplast or PM location of this enzyme drives the protein's structurally congruent potential to work in a reversible manner -either in the synthesis or hydrolysis of its substrate, PPi.…”
mentioning
confidence: 93%
“…8,[11][12][13] Thermodynamic, 14 genetic, immunohistochemical, and physiological evidence 8,15,16 is consistent with a reverse PPi synthase activity of H C -PPase at the PM in the phloem, where it plays an important role in PPi homeostasis and photosynthate partitioning. 10,[15][16][17] We contend that the magnitude of proton gradients associated with the tonoplast or PM location of this enzyme drives the protein's structurally congruent potential to work in a reversible manner -either in the synthesis or hydrolysis of its substrate, PPi. 10,17 That the proton gradient drives the hydrolytic or synthetic activity of H C -PPase is corroborated by experimental evidence in maize coleoptiles and oranges.…”
mentioning
confidence: 93%